Skeletal progenitor cells and ageing human populations. - Oreffo, R; Bord, S; Triffitt, J (1998)
1. Stem and progenitor cells present within bone marrow give rise to colony forming units-fibroblastic (CFU-F) which can differentiate into fibroblastic, osteogenic, myogenic, adipogenic and reticular cells. The decrease in skeletal bone formation and rate of fracture repair observed with ageing and in osteoporosis has been suggested to be due to a decrease in numbers of these progenitors, but human studies are limited. 2. We have tested the potential to form CFU-F in a total of 99 patients undergoing corrective surgery (16 controls, 14-48 years of age) or hip arthroplasty for osteoarthritis (57 patients, 28-87 years of age) or osteoporosis (26 patients, 69-97 years of age). Total colony number, alkaline phosphatase-positive colony number and colony size were determined. 3. No decrease in colony forming efficiency under the culture conditions used was observed in all populations examined irrespective of age, disease or gender, as determined by the lack of correlation between colony formation and age. 3. Examination of colony sizes showed a significant reduction in colony size with age in osteoarthritis and in control populations indicating a change in cellular proliferative potential with age. 4. Examination of number and percentage of alkaline phosphatase-positive CFU-F showed a significant decrease in osteoporotic patients compared with controls and osteoarthritis patients, indicating altered differentiation potential. 5. These results suggest that the reduction in bone mass with ageing may be due to reduction of the proliferative capacity of progenitor cells or their responsiveness to biological factors leading to alteration in subsequent differentiation. The maintenance of CFU-F number and alkaline phosphatase activity in these osteoarthritis patients may, in part, explain the inverse relationship observed for the preservation of bone mass between generalized osteoarthritis and primary osteoporosis.